KINETICS OF THE ACTION OF AMPICILLIN ON ESCHERICHIA COLI - Seligman, Stephen J. (1963)
Seligman, Stephen J. (University of California, Los Angeles) and William L. Hewitt. Kinetics of the action of ampicillin on Escherichia coli. J. Bacteriol. 85:1160–1164. 1963.—The curve of the number of viable Escherichia coli after exposure to ampicillin can be divided into three phases: a lag phase, a rapid bactericidal phase, and a slow bactericidal phase. Some of the variables affecting the magnitude of the first two of these phases were investigated. Progressive lowering of drug concentration resulted in prolongation of the lag phase and decrease in slope and extent of the rapid bactericidal phase. The production of elongated gram-negative forms and the emergence of a mutant with increased penicillinase activity complicated interpretation of the lower dose curves. With sufficient drug concentration, the length of the lag phase and the slope of the rapid bactericidal curve were independent of the size of inoculum up to 10(8) organisms. Varying pH revealed that maximal activity, as measured by the shortest lag phase and steepest slope of the rapid bactericidal phase, was present at slightly acid pH levels. Increasing pH resulted principally in prolongation of lag phase. With greater acidity, decrease in slope of the rapid bactericidal phase was more prominent. Cultures studied under conditions of lessened metabolic activity exhibited prolonged lag phase and decreased slope and extent of rapid bactericidal phase.